Characterization of Cellular Binding Sites and Interactive Regions within Reactants Required for Enhancement of Plasminogen Activation by tPA on the Surface of Leukocytic Cells - Félez, Jordi; Miles, Lindsey A; Fabregas, Pere; Jardi, Merce; Plow, Edward F; Lijnen, Roger H (Thrombosis and Haemostasis, 1996)
Plasminogen and tPA bind to a common set of binding sites on nucleated cells. To assess the functional consequences of cellular binding, we have measured the kinetic changes induced by plasminogen activation by tPA on cell surfaces. These studies were carried out with U937 and THP-1 monocytoid cells, with Raji, Nalm6 and Molt4 lymphoid cells and with peripheral blood monocytes and neutrophils. The interactions of plasminogen and tPA with cells induced an increase in the rate of plasmin generation which depended upon the cell concentration. With saturating amounts of U937 monocytoid cells (1.25 × 105/ml) the rate of plasmin generation was 0.39 nM.s-1 versus 0.07 and 0.09 nM.s-1 without cells or without tPA, respectively. The catalytic efficiency of Glu- or Lys-plasminogen activation by tPA increased by 7.2- and 24.2-fold, respectively. These changes were induced by a 72-242-fold reduction in the Km of these interactions which was in the range of 0.3-0.9 µM. These values are below the plasminogen concentration in plasma (1-2 µM). Moreover, we provide new data indicating that 1) only a specific subset of plasminogen binding sites, i.e. molecules exposing carboxyl terminal lysines on the cell surface, promotes plasminogen activation on cells; 2) the first four kringles of plasminogen and the finger of tPA are critical for enhanced plasmin generation on cell surfaces; 3) the simultaneous co-localization of tPA with plasminogen on cell surfaces is required for enhanced plasminogen activation; 4) modulation of plasminogen/tPA receptor expression induces concomitant modulation of the stimulatory effects of cells on plasminogen activation and 5) in a direct comparison, the mechanism by which cells and fibrin fragments accelerate plasminogen activation are similar but not identical. These data suggest that modulation of plasminogen/tPA binding sites permits local and efficient generation of plasmin on cell surfaces.